Strengthening integrated community case management through digitalization and performance management in Busia County, Kenya - Njoroge, Joseph Kyalo; Gitau, Tabither Muthoni; Yegon, Erick Kiprotich; Mwita, Nzomo; Koimur, Alice; Ochieng, Marlyn; Omollo, Rhonnie; Amihanda, Rosebellah (Frontiers in Public Health, 2025)
Kenya continues to face a high burden of childhood mortality driven by preventable illnesses such as diarrhea, malaria, and pneumonia. Integrated community case management (iCCM) offers a strategy for mitigating this burden through community-level diagnosis, treatment, and referral. This study assessed the role of digitalization and performance management in enhancing the effectiveness of the iCCM strategy in Busia County. Using a quasi-experimental design, a comparison of iCCM intervention outcomes in Nambale sub-county with a non-iCCM comparison site in Teso South sub-county was done. Data were collected through household surveys and in-depth interviews. Results showed a significant improvement in healthcare-seeking behavior in the intervention site, with 56% of caregivers reporting that they sought care for pneumonia on the same day of symptom onset, compared to 35% in the comparison site (p = 0.031). Additionally, findings indicate that CHPs were a preferred point of care for iCCM cases in the intervention site, managing 38% of malaria cases, 19% of pneumonia cases, and 25% of diarrhea cases at the community level. This contrasts with the comparison site, where only 16, 3.7, and 0% of malaria, pneumonia, and diarrhea cases, respectively, were managed by CHPs, all differences being statistically significant (p < 0.05). The significantly higher proportion of iCCM cases managed by CHPs in the intervention site was associated with a lower reliance on facility-based care. Only 42% of ARI cases were managed at government facilities in the intervention site compared to 62% in the comparison site (p = 0.024), while just 1.9% of cases were handled at private facilities in the intervention site versus 12.2% in the comparison site (p = 0.03). These improvements were made possible by the integration of the digital tools and robust performance management practices. This combination enhanced CHWs effectiveness, strengthened health seeking behaviors, and contributed to the overall success of the iCCM strategy in the intervention area. In conclusion, digitalization and robust performance management strengthen the iCCM strategy leading to improved by improving health care seeking for childhood illnesses behaviors and reduce health system burden in low-resource settings.